ROLE AND SIGNIFICANCE OF FOLKLER MUSIC IN THE UPBRINGING OF CHILDREN OF PRESCHOOL AGE - NURULLAYEV, FARRUX (Центр Научных Публикаций (buxdu.uz), 2021)
The word folklore is an English word composed of two words "folk" - people "lor" - teaching. So, folklore is folk wisdom. Folklore has no author. This is a special art - folk songs dances, legends and fairy tales, rituals, beliefs, etc. People who once created them were passed on to others by word of mouth, so folklore has survived to this day without leaving the names of its creators. Folklore accompanies a person from birth, taking care of in childhood, right up to the transition to youth.